Local anisotropic mechanical properties of human carotid atherosclerotic plaques – Characterisation by micro-indentation and inverse finite element analysis. (March 2015) - Chai, Chen-Ket; Akyildiz, Ali C.; Speelman, Lambert; Gijsen, Frank J.H.; Oomens, Cees W.J.; van Sambeek, Marc R.H.M.; Lugt, Aad van der; Baaijens, Frank P.T.
Abstract: Biomechanical models have the potential to predict failure of atherosclerotic plaques and to improve the risk assessment of plaque rupture. The applicability of these models depends strongly on the used material models. Current biomechanical models employ isotropic material models, although it is generally accepted that plaque tissue behaves highly anisotropic. The aim of the present study is to determine the local anisotropic mechanical properties of human atherosclerotic plaque tissue by means of micro-indentation tests. The indentation was performed on top of an inverted confocal microscope allowing the visualisation and quantification of the collagen fibre deformations perpendicular to the indentation direction of the plaque. Based on this, the anisotropic properties of plaque tissue perpendicular to the indentation direction (middle of the fibrous cap, shoulder of the cap, remaining intima tissue) were derived. There were no significant differences between the different indentation locations for the fibre stiffness (total median 80.6 kPa, 25th–75th percentile 17.7–157.0 kPa), and fibre dispersion.